Espèces emblématiques et gestion de la mer, regards pluridisciplinaires en sciences sociales et nouvelles approches méthodologiques dans l’outre-mer indo-pacifique - Sabinot, Catherine; Delebecque, Solène; Cillaurren, Espérance; Fossier, Camille; Pennober, Gwenaëlle; Rodary, Estienne; David, Gilbert (Norois, 2021)
How can the knowledge, social and cultural values attributed to animals and marine territories in New Caledonia and Reunion be understood in a sensitive manner and made useful and understandable by those who construct and enforce policies? Can disciplinary and interdisciplinary approaches in the humanities and social sciences accurately reflect local realities while translating them in such a way that they have the same operational significance as the indicators determined by the study of the biology and ecology of natural habitats? This article aims to answer these two questions, which have motivated the researchers of the ESPAM program (Emblematic Species, Social Acceptance, Marine Protected Area) funded by the Fondation de France.We show how a methodological development combining qualitative and quantitative approaches allows us to better understand cultural and social values according to marine environment and to produce dialogue tools accessible to various territorial actors. We present the contexts of the two overseas territories that gave rise to the need to produce innovative methodological tools, describe the interdisciplinary approach implemented, and share some of the results illustrated by the visuals produced for the population and managers. Among other things, the reader will be able to discover the 137 species characterized as emblematic in the study areas as well as the reasons that lead the populations of these islands to consider these species as more important than others. Comment appréhender de manière sensible les savoirs, les valeurs sociales et culturelles accordées aux animaux et aux territoires marins en Nouvelle-Calédonie et à La Réunion et les rendre utiles et compréhensibles par ceux qui construisent les politiques et les font appliquer ? Des approches disciplinaires et interdisciplinaires en sciences humaines et sociales peuvent-elles rendre compte fidèlement des réalités locales tout en les traduisant de sorte qu’elles aient une portée opérationnelle au même titre que les ...